Strategi Pemberdayaan Ekonomi Dalam Meningkatkan Kesejahteraan Santri Dan Warga Masyarakat Pondok Pesantren Hidayatullah Balikpapan Dan Pondok Pesantren Syaichona Cholil Balikpapan - Hakim, Abdul; Pancasilawati, Abnan; Hasan, Muhammad (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This article discusses the economic empowerment strategies implemented at two Islamic boarding schools in Balikpapan—Pondok Pesantren Hidayatullah and Pondok Pesantren Syaichona Cholil—which function not only as educational institutions but also as agents of economic development. The empowerment strategies include structural economic transformation, resource allocation, institutional strengthening, technological advancement, and human resource development. Various business units have been developed, such as cooperatives, Madani markets, skills training programs, agriculture, retail shops, and Islamic financial services, involving both students and the surrounding community. The research adopts a qualitative case study approach, using observation, in-depth interviews, and documentation as data collection techniques. The findings show that both pesantrens successfully implemented strategies based on local potential and Islamic values, contributing to economic self-reliance. Key success factors include strong leadership support, a spirit of independence, and active community involvement.